'World Trade Center, Accra': production of urban space for the continued peripheral linkage of Ghana under globalization. Issue 1 (2nd January 2021) - Yeboah, Ian E. A.; Maingi, John K.; Arku, Godwin
ABSTRACT: West Ridge in Accra, Ghana, a residential enclave for colonial administrators is being produced again to serve as the financial center of the country. The area is identified after one building: World Trade Center, Accra (WTCA). We map the transformation of WTCA and situate its emergence within three frameworks. We argue that the continued peripheral linkage of Ghana and the unwillingness of global capital to bear the overhead cost of extracting wealth from the country have created a vacuum for semi-peripheral, peripheral, and state capital to serve the financial needs of global capital. Ghana's financial structural adjustment facilitated these processes.